Prognostic value of Inflammatory Cytokine Levels (TNF-α, procalcitonin (PCT), interferon gamma (IFN-γ), IL-2, IL-6, and IL-10), Clinical Efficacy, and Prognosis of Hybrid Artificial Liver Support System in the Treatment of Chronic Liver Failure: Prognostic value of Inflammatory Cytokine Levels - Nan, Xueping (Journal of Medical Biochemistry, 2025)
Introduction: it aimed to explore effectiveness and security of the hybrid artificial liver support system (HALSS) for chronic liver failure (CLF) patients, and analyze inflammatory response and prognosis of patients.Material and Method: 126 patients with CLF divided into plasma exchange group (PEG), double plasma molecular absorb system group (DPMASG), and combination group (CG). Liver and kidney function, blood coagulation function, and T lymphocyte subgroup level change were compared, analysis of short-term clinical curative effect and adverse reactions after treatment.Result: as against PEG and DPMASG, in CG, peripheral blood alanine aminotransferase (ALT), aspartate aminotransferase (AST), total bilirubin (TBil), total biliary acid, creatinine (Cr),international normalized ratio (INR), prothrombin time (PT) dropped and cholinesterase (ChE), albumin, prothrombin time activity (PTA) rose; peripheral blood CD4+ rose, CD8+ dropped, and inflammatory cytokine TNF-α, procalcitonin (PCT), interferon gamma (IFN-γ), IL-2, IL-6, and IL-10 levels were lower; model for end-stage liver disease (MELD) and Child-Turcotte-Pugh (CTP) score were lower (all P < 0.05). In PEG, DPMASG, and CG, the clinical total effective rate was 76.3%, 78.9%, and 92.0%, respectively; the adverse reaction rate (ARR) was 18.4%, 13.2%, and 8.0%; 1-year overall survival rate (SR) for follow-up was 18.4%, 21.1%, and 36.0%. CG had higher clinical effectiveness and 1-year overall survival, and lower rate of adverse reaction (P < 0.05).Conclusion: PE+DPMAS can effectively improve the CLF, liver and kidney function, and blood coagulation function in patients.
Keywords: TNF-α, procalcitonin (PCT), interferon gamma (IFN-γ), IL-2, IL-6, and IL-10 ,CLF; PE; DPMAS; adverse reactions; long-term survival